Microstructural injury to the optic nerve with vigabatrin treatment in West syndrome: A DTI study - Junjie Hu; Li Chen; Gongwei Zhang; Yu Fang; Huiting Zhang; Yilian Li; Jianxiang Liao; Cailei Zhao (Scientific Reports)
Abstract To evaluate optic nerve injury associated with vigabatrin treatment in children with West syndrome using diffusion tensor imaging. Thirty-five children with West syndrome (aged 9 days–22 months) were retrospectively analyzed and grouped as follows: (1) vigabatrin with symmetrical thalamic abnormalities, (2) vigabatrin without thalamic abnormalities, and (3) controls on other anti-seizure medications. Fractional anisotropy and apparent diffusion coefficient values of the optic nerves were assessed. ROC curves were used to determine fractional anisotropy thresholds for optic nerve injury. fractional anisotropy values in group 1 were significantly lower than those in the control group (P < 0.05), while apparent diffusion coefficient values showed no significant differences. fractional anisotropy values increased significantly after vigabatrin discontinuation (P < 0.05). ROC analysis yielded an fractional anisotropy cut-off value of 304 with 63.6% sensitivity and 100% specificity. fractional anisotropy values are a sensitive imaging biomarker for detecting vigabatrin-related optic nerve injury in West syndrome, particularly when thalamic abnormalities are present. These changes appear reversible after stopping vigabatrin.